An Evaluation of Metronidazole Degradation in a Plasma-Assisted Rotating Disk Reactor Coupled with TiO2 in Aqueous Solution. (November 2021) - Cai, Yong; Chu, Guang-Wen; Luo, Yong; Su, Meng-Jun; Wang, Bao-Ju; Sun, Bao-Chang; Chen, Jian-Feng
Abstract: Pollution involving pharmaceutical components in bodies of water is an increasingly serious environmental issue. Plasma discharge for the degradation of antibiotics is an emerging technology that may be relevant toward addressing this issue. In this work, a plasma-assisted rotating disk reactor (plasma-RDR) and a photocatalyst—namely, titanium dioxide (TiO2 )—were coupled for the treatment of metronidazole (MNZ). Discharge uniformity was improved by the use of a rotating electrode in the plasma-RDR, which contributed to the utilization of ultraviolet (UV) light radiation in the presence of TiO2 . The experimental results showed that the degradation efficiency of MNZ and the concentration of generated hydroxyl radicals respectively increased by 41% and 2.954 mg∙L −1 as the rotational speed increased from 0 to 500 r∙min −1 . The synergistic effect of plasma-RDR plus TiO2 on the generation of hydroxyl radicals was evaluated. Major intermediate products were identified using three-dimensional (3D) excitation emission fluorescence matrices (EEFMs) and liquid chromatography–mass spectrometry (LC-MS), and a possible degradation pathway is proposed herein. This plasma-catalytic process has bright prospects in the field of antibiotics degradation.